Autosomal dominant polycystic kidney disease in Colombia - Jessica T. Camargo; Camilo A González; Lina Herrera; Nancy Yomayusa-González; Milciades Ibañez; Ana M. Valbuena-García; Lizbeth Acuña-Merchán (BMC Nephrology, 2023)
Abstract Background Autosomal dominant polycystic kidney disease (ADPKD) is the most common genetic cause of chronic kidney disease (CKD) that requires dialysis. Knowing geographical clusters can be critical for early diagnosis, progression control, and genetic counseling. The objective was to establish the prevalence, geographic location, and ethnic groups of patients with ADPKD who underwent dialysis or kidney transplant in Colombia between 2015 and 2019. Methods We did a cross-sectional study with data from the National Registry of Chronic Kidney Disease (NRCKD) managed by the High-Cost Diseases Fund (Cuenta de Alto Costo [CAC] in Spanish) between July 1, 2015, and June 30, 2019. We included Colombian population with CKD with or without renal replacement therapy (RRT) due to ADPKD. Crude and adjusted prevalence rates were estimated by state and city. Results 3,339 patients with ADPKD were included, period prevalence was 9.81 per 100,000 population; there were 4.35 cases of RRT per 100,000 population, mean age of 52.58 years (± 13.21), and 52.78% women. Seventy-six patients were Afro-Colombians, six were indigenous, and one Roma people. A total of 46.07% began scheduled dialysis. The highest adjusted prevalence rate was in Valle del Cauca (6.55 cases per 100,000 population), followed by Risaralda, and La Guajira. Regarding cities, Cali had the highest prevalence rate (9.38 cases per 100,000 population), followed by Pasto, Medellin, and Bucaramanga. Conclusions ADPKD prevalence is lower compared to Europe and US; some states with higher prevalence could be objective to genetic prevalence study.